A desalination system with efficiency approaching the theoretical limits. Issue 48 (20th October 2016) - Davies, Philip A.; Wayman, James; Alatta, Chioma; Nguyen, Kim; Orfi, Jamel
Abstract: The objective of this project is to design a new desalination system with energy efficiency approaching the theoretical thermodynamic limit—even at high recovery ratio. The system uses reverse osmosis (RO) and a batch principle of operation to overcome the problem of concentration factor which prevents continuous-flow RO systems from ever reaching this limit and thus achieving the minimum possible specific energy consumption, SEC. Batch operation comprises a cycle in three phases: pressurisation, purge, and refill. Energy recovery is inherent to the design. Unlike in closed-circuit desalination (CCD), no feedwater is added to the pressure circuit during the pressurisation phase. The batch configuration is compared to standard configurations such as continuous single-stage RO (with energy recovery) and CCD. Theoretical analysis has shown that the new system is able to use 33% less energy than CCD at a recovery ratio of 80%. A prototype has been constructed using readily available parts and tested with feedwater salinities and recovery ratios ranging from 2, 000 to 5, 000 ppm and 17.2–70.6%, respectively. Results compare very well against the standard configurations. For example, with feedwater containing 5, 000 ppm NaCl and recovery ratio of 69%, a hydraulic SEC of 0.31 kWh/m 3 was obtained—better than the minimum theoretically possible with a single-stage continuous flow system with energy recovery device.